Live Streaming, Electronic Word of Mouth, and Brand Trust on Consumer Purchase Decisionsat Parfume Mykonos (Jurnal Manajemen Bisnis, 2024)
This consider points to decide the impact of Live Streaming, Electronic Word of mouth, and Brand Trust on Consumer Purchasing Decisions for Mykonos Aroma in Sidoarjo. This consider employments quantitative inquire about with speculation testing. The test utilized in this think about summed to 96 respondents. The explanatory instrument utilized in this investigate is way investigation procedure, carried out utilizing SmartPLS (Fractional Slightest Square) computer program adaptation 4.0 for Windows. Essential information in this ponder were gotten from a survey whose estimations utilized a Likert scale that had been tried for legitimacy and unwavering quality. The comes about of this ponder demonstrate that (1) Live Streaming affects purchasing decisions, (2) electronic word of mouth affects purchasing decisions, (3) brand trust affects purchasing decisions.